Matched pitch rate extensions to dynamic stall on rotor blades. (May 2017) - Müller-Vahl, Hanns Friedrich; Pechlivanoglou, Georgios; Nayeri, Christian Navid; Paschereit, Christian Oliver; Greenblatt, David
Abstract: Dynamic stall on both horizontal axis and vertical axis wind turbine blades is accompanied by simultaneous changes in pitch and surge, but this simultaneous effect has never been documented. Using a unique unsteady wind tunnel, synchronous oscillations in angle of attack and flow speed were considered on two prototypical wind turbine blades. At a steady freestream, the concept of matched pitch rate was observed to be valid for large positive and negative pitch angles. In the presence of an unsteady stream, matching the flow speed as well as the pitch angle and its time derivative during pitch-up produced excellent correspondence between lift, drag and moment coefficients throughout the entire dynamic stall event. Highlights: Wind turbine blade dynamic stall is studied in a custom-built unsteady wind tunnel facility. The synchronous variations in angle of attack and relative flow speed are reproduced. The matched pitch rate concept is extended to conditions representative of wind turbine rotor blades. A close agreement between the matched data sets is observed.